KEBERLANJUTAN RANTAI PASOK INDUSTRI KECIL DAN MENENGAH (IKM) ALAS KAKI DI KABUPATEN DAN KOTA BOGOR - Wilda Sukmawati; Machfud; Ono Suparno; Aji Hermawan (Jurnal Teknologi Industri Pertanian, 2020)
Measurement of supply chain sustainability in the footwear industry is limited to measurements on craftsmen as footwear makers in the District and City of Bogor. The purpose of this study was to obtain a footwear industry supply chain sustainability index in the District and City of Bogor as an industrial centre in the West Java region. The method approach taken was Multidimensional Scaling (MDS) using Rapfish software. This study analyzed three dimensions, namely economic, social and environment. The indicators used for the economic dimension were net profit, sales targets, production capacity, labour income, product quality, market access, investment for the environmental improvement, research and technology development. Indicators measured for the social dimension were employment opportunities for the local workers, human reource skills, easiness access to health, use of equipment, work safety, workplace quality, air quality of production rooms, workforce training, number of products returned, and certification in the social field. On the environmental dimension, the indicators measured were the reduction in the amount of energy used, the use of environmentally friendly materials, the level of waste management, measurement and reduction of emissions produced, certification in the environmental field, use of materials from local suppliers. The results of measurement of the footwear industry sustainability indexes were less sustainable for the economic and social dimensions, whereas for the environment dimension indexed was not sustainable. In leverage analysis, indicators that influenced to increase the index for the economic dimension were market access and labour income, the social dimension were the quality of the production room air and the use of safety equipment, and the environmental dimension were the level of waste management, measurement and emission reduction. Keywords: sustainability. footwear, MDS